Inclusive Madrasah Teacher Competency Crisis Policy Recommendations from the Minister of Religious Affairs for Standardizing Human Resources and Personalizing Services - Ririn Dwi Agustin (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
This policy paper addresses the systemic challenges in ensuring the quality and personalization of inclusive education services in madrasas, focusing on the failure of the Ministry of Religious Affairs to strengthen support for integrated human resource (HR) development policies. Although the law has provided for inclusive services and Special Guidance Teachers (GPK), implementation in madrasas is hampered by the limited professional competence of classroom teachers and the absence of structured and ongoing Grand Design training. Data shows that less than twenty-five percent of teachers in inclusive madrasas feel confident in designing Individual Learning Programs (PPI), the current ratio of Students with Special Needs (PDBK) per GPK is far below the ideal standard, indicating that a decent, affordable mandate is merely an administrative formality. The writing method used is a qualitative policy analysis, beginning with identifying the root of the problem through literature and regulatory studies, followed by a priority analysis using the USG (Urgency, Seriousness, Growth) method to develop teacher competency development as the main focus. Next, three alternative policy regulations are proposed, which are then evaluated comparatively using William N. Dunn's Policy Alternative Scoring Theory based on the criteria of effectiveness, efficiency, adequacy, equity, and responsiveness. The analysis results show that the Alternative Issuance of the Minister of Religious Affairs Regulation (PMA) concerning Inclusive Competency Standards for Madrasah Teachers received the highest score. Therefore, the paper's primary policy recommendation is to urge the Ministry of Religious Affairs to issue the Ministerial Regulation as a binding regulatory solution to standardize GPK human resources and grant PDBK the right to effective and personalized learning